How do you find the asymptotes for #f(x)=(2x^3+3x^2+x)/(6x^2+x-1)#?

Answer 1

The vertical asymptote is #x=1/3#. No horizontal asymptote. The slant asymptote is #y=1/3x+4/9#

The numerator is

#2x^3+3x^2+x=x(2x^2+3x+1)#
#=x(2x+1)(x+1)#

The denominator is

#6x^2+x-1=(3x-1)(2x+1)#

The function is

#f(x)=(2x^3+3x^2+x)/(6x^2+x-1)#
#=(xcancel(2x+1)(x+1))/((3x-1)cancel(2x+1))#
#=(x(x+1))/(3x-1)#
As the denominator must de #!=0#, therefore
#3x-1!=0#, #=>#, #x!=1/3#
The vertical asymptote is #x=1/3#

There is no horizontal asymptote, as

#lim_(x->oo)f(x)=lim_(x->oo)(x^2)/(3x)=lim_(x->oo)x/3=+oo#
#lim_(x->-oo)f(x)=lim_(x->-oo)(x^2)/(3x)=lim_(x->-oo)x/3=-oo#
As the degree of the numerator is #># the degree of the denominator, there is a slant asymptote.

Perform a long division

#color(white)(aaaa)##x^2+x##color(white)(aaaa)##|##3x-1#
#color(white)(aaaa)##x^2-1/3x##color(white)(aaaa)##|##1/3x+4/9#
#color(white)(aaaaa)##0+4/3x#
#color(white)(aaaaaaa)##+4/3x+0#
#color(white)(aaaaaaa)##+4/3x-4/9#
#color(white)(aaaaaaaaa)##+0+4/9#

Therefore,

#f(x)=(x^2+x)/(3x-1)=(1/3x+4/9)+(4/9)/(3x-1)#
#lim_(x->+oo)(f(x)-(1/3x+4/9))=lim_(x->+oo)(4/9)/(3x-1)=0^+#
#lim_(x->-oo)(f(x)-(1/3x+4/9))=lim_(x->-oo)(4/9)/(3x-1)=0^-#

The slant asymptote is

#y=1/3x+4/9#

graph{(y-(x(x+1))/(3x-1))(y-1/3x-4/9)=0 [-4.382, 4.386, -2.19, 2.193]}

Sign up to view the whole answer

By signing up, you agree to our Terms of Service and Privacy Policy

Sign up with email
Answer 2

To find the asymptotes of the rational function ( f(x) = \frac{2x^3 + 3x^2 + x}{6x^2 + x - 1} ), you need to determine both vertical and horizontal asymptotes.

Vertical asymptotes occur where the denominator equals zero and the numerator doesn't. To find vertical asymptotes, solve (6x^2 + x - 1 = 0) for (x).

Horizontal asymptotes can be found by comparing the degrees of the numerator and denominator. If the degree of the numerator is greater than the degree of the denominator, there is no horizontal asymptote. If the degree of the numerator is less than the degree of the denominator, the horizontal asymptote is at (y = 0). If the degrees are equal, divide the leading coefficients of both terms to find the horizontal asymptote.

So, to summarize:

  1. Find vertical asymptotes by solving (6x^2 + x - 1 = 0) for (x).
  2. Determine horizontal asymptotes by comparing the degrees of the numerator and denominator.
Sign up to view the whole answer

By signing up, you agree to our Terms of Service and Privacy Policy

Sign up with email
Answer from HIX Tutor

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

Not the question you need?

Drag image here or click to upload

Or press Ctrl + V to paste
Answer Background
HIX Tutor
Solve ANY homework problem with a smart AI
  • 98% accuracy study help
  • Covers math, physics, chemistry, biology, and more
  • Step-by-step, in-depth guides
  • Readily available 24/7